Metarhizium brunneum Petch Fungi is Effective as a Bioinsecticide Against Coptotermes curvignathus Holmgren Termite Pests in the Laboratory - Muhammad Sayuthi; Teguh Santoso; Iswadi Iswadi (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract: Nutmeg is a plantation crop and has high economic value. Currently, the cultivation of nutmeg is experiencing many obstacles. One of them is termite pests. So far, the control is carried out using chemical insecticides and hurts the environment. Therefore it is necessary to control other environmentally friendly ways, and one of them is by using the fungi M. brunneum as an ecologically friendly bioinsecticide. The purpose of this study was to analyze the effectiveness of M. brunneum as a bioinsecticide against the termite C. curvignathus as an essential pest in nutmeg plantations. This research using a completely randomized design (CRD). The results showed that the mean percentage viability of M. brunneum conidia at each observation time was classified as useful. The germination of conidia increased to 89.78 % after 72 hours of observation. Conidia density 103/ mL distilled water. The highest mortality rate of C. curvignathus was found at a density of 1010 conidia/ mL of distilled water. The mean time of death for C. curvignathus after application of conidia density treatment of 1010/ mL of distilled water was 2.15 days and the death of C. curvignathus was 3.35 days using conidia density treatment 103/ mL of distilled water. 1 day after application reaches 33.20 % and increases to observation at 5 days after application reaches 100 %. The highest food inhibition occurred in treatment 1010/ mL distilled water (65.81 %) which was significantly different from treatment 105/ mL distilled water (43.23 %), and 103/ mL distilled water (41.61 %) and control (0.00).Abstrak: Pala merupakan tanaman perkebunan dan bernilai ekonomi tinggi. Pada saat ini budidayanya mengalami banyak hambatan. Satu diantaranya adalah serangan hama rayap. Selama ini  pengendalian hama rayap dilakukan dengan menggunakan insektisida kimia dan berpengaruh negatif terhadap lingkungan. Oleh karenanya perlu pengendalian cara lain yang ramah lingkungan dan satu diantaranya dengan menggunakan cendawan M. brunneum sebagai bioinsektisida yang ramah lingkungan. Tujuan dari penelitian ini adalah menganalisis efektivitas M. brunneum sebagai bioinsektisida terhadap hama rayap C. curvignathus. Penelitian ini dilaksanakan di Laboratorium Hama Tanaman dan Laboratorium Dasar Proteksi Tanaman Program Studi Proteksi Tanaman Fakultas Pertanian Universitas Syiah Kuala, sejak bulan Februari hingga September 2018, dengan menggunakan Rancangan Acak Lengkap (RAL). Hasil penelitian menunjukkan bahwa persentase viabilitas rata-rata dari konidia M. brunneum pada setiap waktu pengamatan tergolong efektif. Perkecambahan konidia semakin meningkat hingga mencapai 89,78 % setelah diamati pada jam yang ke 72. Rata-rata waktu kematian rayap C. curvignathus setelah aplikasi perlakuan kerapatan konidia 1010/ mL akuades adalah 2,15 hari dan terjadi kematian rayap C. curvignathus 3.35 hari dengan menggunakan perlakuan kerapatan konidia 103/ mL akuades. Rata-rata mortalitas tertinggi rayap C. curvignathus ditemukan pada perlakuan kerapatan konidia 1010/mL aquades. 1 HSA mencapai 33,20% dan meningkat hingga pengamatan pada 5 HSA mencapai 100%. Daya hambat makan tertinggi terjadi pada perlakuan 1010/ mL aquades (65,81%) yang berbeda nyata dengan perlakuan 105/mL aquades (43,23%) dan 103/ mL aquades (41,61%) serta kontrol (0,00%).